Pengaruh Penambahan Natrium Hipoklorit terhadap Kuat Tarik Bioplastik Berbahan Dasar Umbi Bira (Alocasia macrorrhizos) - Lindasekar Utami; Zulkarnain; Qomaria Ahmad; Suci Pebriyanti Putri (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to investigate the effect of sodium hypochlorite addition on the tensile strength of bioplastics derived from giant taro tuber starch (Alocasia macrorrhizos). The research employed an experimental method with variations in sodium hypochlorite addition of 10%, 20%, 30%, and 40%. Bioplastic samples were prepared through starch extraction, followed by mixing with sodium hypochlorite, glycerol, and water, and subsequently tested for tensile strength using a tensile testing machine. The results revealed that the highest tensile strength value, 1300 N/m², was achieved in the sample containing 40% sodium hypochlorite, satisfying the Indonesian National Standard (SNI). It is concluded that increasing the percentage of sodium hypochlorite positively affects the tensile strength of the resulting bioplastic.